A LEGAL-EMPIRICAL ANALYSIS OF OWNERSHIP AND UTILIZATION OF OFFICIAL HOUSES BY RETIRED EMPLOYEES OF STATE-OWNED PLANTATION ENTERPRISES: A CASE STUDY OF PTPN IX AND IV: ANALISIS YURIDIS -EMPIRIS ATAS KEPEMILIKAN DAN PEMANFAATAN RUMAH DINAS OLEH PENSIUNAN KARYAWAN BUMN PERKEBUNAN: STUDI KASUS PTPN IX DAN IV - Alfian Fauzan; Dhiauddin Tanjung; Akmaluddin Syahputra (SOSIOEDUKASI, 2025)
This study aims to analyze the legal basis for the management and use of employee official housing at PTPN IX and PTPN IV, to examine the legal status of official residences occupied by employees after retirement, and to identify the underlying factors and the efforts made by the companies to resolve the issue. It also seeks to explore the social, economic, and legal implications of retired plantation employees continuing to occupy official housing. The research employs a qualitative approach with a juridical-empirical method, combining normative legal analysis with field observations through case studies of PTPN IX and PTPN IV. The results show that the legal foundation for providing official housing is derived from national regulations such as the State-Owned Enterprises Law, the Plantation Law, and internal company policies, which classify official residences as state property (BMN) allocated for use only during active employment. The findings reveal that many retired employees continue to occupy these houses due to economic constraints, lack of private housing, and a social perception that the houses are part of their earned rights. On the other hand, the companies face difficulties in enforcing eviction due to social resistance and weak regulatory enforcement mechanisms. The discussion indicates that this issue extends beyond legal dimensions, creating significant social and economic repercussions. From the perspective of agrarian and civil law, occupying official residences after retirement without legal authorization constitutes unlawful possession of state property. Socially, the tension between companies and retirees can escalate into community-level conflicts. The study emphasizes the need for policy reform and a more adaptive legal approach that considers the socio-economic conditions of retirees, in line with the Islamic legal renewal framework that upholds justice and public welfare.